Upper Palaeolithic site complex at Csécse-Szőlős-domb (Cserhátalja, Nógrád County, Northern Hungary) - Attila Péntek; Krisztián Zandler; Szilvia Guba; Nicklas Larsson (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
This paper presents the find material of a new open-air Upper Palaeolithic site located on the outskirts of Csécse in Cserhátalja, between the Zagyva River and the Szuha Stream. Its topographic position is similar to other Upper Palaeolithic sites in the Cserhát Mountains. Part of the finds were collected by agronomist László Tóth, while the rest were found by the authors later, following the rediscovery of the site in 2017. The appearing raw materials are primarily limnic silicites of Cserhát origin and local siliceous pebbles, accompanied by a low proportion of erratic flint (absent from known Late Middle Palaeolithic lithic industries characterised by leaf-shaped forms); in contrast, the metarhyolite characteristic of said industries is completely absent from the site. The assemblage gives the impression of a flake industry, as blades and blade tools are present in low proportions. The predominant type is end-scrapers with a significant proportion of high-nosed and carenoid Aurignacian variants. Bifacial tools are completely absent, and the proportion of side-scrapers is low. The significance of the assemblage—rich in end-scrapers and relying mainly on local raw materials—lies in that it likely represents an early Aurignacian facies otherwise not known from the Northern Hungarian Mountains. Its further investigation by excavation would be important.